Evaluation of near infrared and nuclear magnetic resonance spectroscopy for rapid quality control of South African extra ﻿virgin olive oils - Eberle, Kerstin (Stellenbosch : University of Stellenbosch, 2006)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2005.